Data regarding articles retracted from PubMed indexed dental journals from India - Thorakkal Shamim (Data in Brief, 2018)
This data aimed to audit the articles retracted from PubMed indexed dental journals from India. The PubMed indexed journals considered are Indian Journal of Dental research, Journal of Indian Society of Periodontology, Contemporary Clinical Dentistry, Journal of Indian Society of Pedodontics and Preventive Dentistry, Journal of Oral and Maxillofacial Pathology and Journal of Indian Prosthodontic Society for type of article, name of dental specialty, topic of individual dental specialties, causes for retraction of article and authorship trend of retracted articles using web-based search. Among PubMed indexed Indian dental journals,the number of retracted articles were as follows: Indian Journal of Dental research (4) followed by Journal of Indian Society of Periodontology (3), Contemporary Clinical Dentistry (3), Journal of Indian Society of Pedodontics and Preventive Dentistry (2), Journal of Oral and Maxillofacial Pathology (2) and Journal of Indian Prosthodontic Society (1). Out of 15 retracted articles from PubMed indexed Indian dental journals, case reports (7) form a major share followed by original articles(6) and review articles (2). Among the dental specialties of retracted articles, oral pathology and microbiology (5) constitute the major share followed by periodontics (4), pedodontics (4), oral medicine and radiology (1) and prosthodontics (1). Duplicate publication (7), plagiarism (5) and authorship dispute (3) are the causes for the retraction of article.